2023
DOI: 10.1111/maps.13946
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the spatial variability of the ~3 μm OH/H2O absorption feature in CM2 carbonaceous chondrites

Abstract: H 2 O and OH are readily detected in hydrated minerals in CM chondrites via reflectance spectroscopy due to their characteristic vibration absorptions at infrared wavelengths. Previous spectroscopic work on bulk powdered CM chondrites has shown that spectral parameters, like the wavelength position of the "3 μm absorption feature," vary systematically with the extent to which the samples have been aqueously altered. However, it is yet unclear how these spectral features may vary across an intact meteorite chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…As demonstrated above, this is primarily because the reflectance spectra of natural, unheated CI chondrites are severely influenced by the presence of phases formed during prolonged terrestrial weathering. In addition to adsorption of atmospheric H 2 O, such weathering has led in particular to the formation of secondary sulfates ( 35 , 56 , 57 ) and ferrihydrites ( 66 , 73 ), rehydration ( 27 , 74 ), and oxidation of Fe 2+ in phyllosilicates ( 13 ). We now discuss each of these points and the corresponding spectral effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As demonstrated above, this is primarily because the reflectance spectra of natural, unheated CI chondrites are severely influenced by the presence of phases formed during prolonged terrestrial weathering. In addition to adsorption of atmospheric H 2 O, such weathering has led in particular to the formation of secondary sulfates ( 35 , 56 , 57 ) and ferrihydrites ( 66 , 73 ), rehydration ( 27 , 74 ), and oxidation of Fe 2+ in phyllosilicates ( 13 ). We now discuss each of these points and the corresponding spectral effects.…”
Section: Discussionmentioning
confidence: 99%
“…S10C) ( 49 , 58 ). A more recent study demonstrated that even low abundances of highly hydrated sulfates can have substantial effects on spectra of CM chondrites, particularly for bulk spectral measurements ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations